2021
DOI: 10.31557/apjcp.2021.22.11.3641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation the Presence of SERPINA5 (Exon 3) and FTO rs9939609 Polymorphisms in Papillary Thyroid Cancer Patients

Abstract: Background: A few researches evaluated the association of polymorphisms at SERPINA5 and fat mass and obesity-associated protein (FTO) genes with papillary thyroid cancer (PTC) globally. Here, we examined the presence of genetic variations within coding exon 3 of SERPINA5 gene and FTO rs9939609 polymorphism in Iranian PTC patients. Methods: A total of 122 patients (42 cases for SERPINA5 and 80 cases for FTO gene) and 120 healthy subjects (40 subjects or SERPINA5 and 80 subjects for FTO gene) were recruited. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, a random-effects model (DerSimonian and Laird method) or fixed-effects model (Mantel-Haenszel method) was used to calculate pooled effect estimates in the presence or absence of heterogeneity, respectively [32][33][34]. Moreover, Hardy-Weinberg equilibrium (HWE) assessed by chi-square test was made in control group of each study [35][36][37][38], P>0.05 were considered to have reliable and representative controls. Subgroup analyses were conducted by stratification of ethnicity to identifying potential source of heterogeneity [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a random-effects model (DerSimonian and Laird method) or fixed-effects model (Mantel-Haenszel method) was used to calculate pooled effect estimates in the presence or absence of heterogeneity, respectively [32][33][34]. Moreover, Hardy-Weinberg equilibrium (HWE) assessed by chi-square test was made in control group of each study [35][36][37][38], P>0.05 were considered to have reliable and representative controls. Subgroup analyses were conducted by stratification of ethnicity to identifying potential source of heterogeneity [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory role of SERPINA5 in hemostasis and thrombosis has been observed in various organs. However, the expression relationship of SERPINA5 in GBM remains unreported, despite its implication in numerous diseases such as osteoarthritis ( 40 ), gastric cancer ( 41 ), and thyroid cancer ( 42 ). Researchers found that LGG patients with high SERPINA5 expression had a poor prognosis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…SERPINA5 regulates hemostasis and thrombosis across multiple organs. There are no reports of the expression relationship of Serpin peptidase inhibitor A member 5 (SERPINA5) in GBM, but a large number of cancers, including hepatocellular carcinoma [35], gastric cancer[36], thyroid cancer [37], are highly expressed in SERPINA5. Researchers found that LGG patients with high SERPINA5 expression had a poor prognosis [38].…”
Section: Discussionmentioning
confidence: 99%